USING PHOTODYNAMIC THERAPY IN ROOT CANAL SYSTEM – A LITERATURE REVIEW - P, AJITHA (Innovare Journal Health Sciences, 2021)
Microorganisms do play in pulpal and periapical infection. Success of endodontic treatment aims at effective eradication of bacteria from the root canal space. This, in turn, prevents further microbial recolonization. Persistent microbial colonies in the root canal lead to failure of the endodontic treatment. With the advent of photodynamic therapy (PDT), a novel invasive approach is aimed at complete disinfection of root canal with elimination of bacteria. Therefore, this paper aims to highlight the efficiency of PDT in endodontics by reviewing the literature published in journals